IDENTIFIKASI HIDANGAN UNTUK SPA (SOLUS PER AQUA) DI KAWASAN PARIWISATA LOVINA - Ni Kadek Sri Wahyuni .; Dra. Damiati, M.Kes .; Luh Masdarini, S.Pd . (Jurnal BOSAPARIS: Pendidikan Kesejahteraan Keluarga, 2017)
Penelitian ini bertujuan untuk identifikasi hidangan untuk SPA (Solus Per Aqua) di kawasan pariwisata Lovina meliputi jenis hidangan untuk SPA (Solus Per Aqua) mulai dari appetizer, main course dan dessert. Penelitian ini dilakukan di Kawasan Pariwisata Lovina dengan mengambil 4 (empat) hotel sebagai tempat penelitian yaitu Sunari Villa’s And SPA Resort, Puri Saron, Bayualit Spa’n Resort dan Sundara Chocolate SPA dengan sumber informan Cheff hotel kawasan pariwisata Lovina. Teknik pengumpulan data dengan metode observasi (observation) dan metode wawancara, sedangkan instrumen penelitian yang digunakan yaitu lembar observasi dan panduan wawancara. Analisis data menggunakan teknik deskriptif kualitatif. Hasil penelitian menunjukkan bahwa hidangan untuk SPA (Solus Per Aqua)di Kawasan Pariwisata Lovina (1) Sunari Villa’s And SPA Resort, hidangan appetizer meliputi tuna fish salad (cold appetizer), cream potato leek soup (hot appetizer), hidangan main course meliputi club house sandwich, BLT sandwich, beef burger dan hidangan dessert meliputi sunari mixed juice (cold dessert) dan indonesia tea (hot dessert). (2) Bayualit Spa’n Resort hidangan appetizer meliputi mix salad (cold appetizer), tomato saup with toas (hot appetizer) hidangan main course meliputi chicken sandwich, club sandwich dan hidangan dessert meliputi mix juice (cold dessert), ginger tea (hot dessert). (3) puri saron, hidangan appetizer meliputi caesar salad (cold appetizer), cream of tomato soup (hot appetizer) hidangan main course meliputi club sandwih, dan hidangan dessert meliputi banana juice (cold dessert) ginger tea (hot dessert). (4) Sundara Chocolate SPA, hidangan appetizer meliputi potato salad (cold appetizer), cream chicken soup (hot appetizer) hidangan main course meliputi club sandwich, smoke beef sandwich, chicken barito dan hidangan dessert meliputi ice ginger chocolate (cold dessert), melamun moctail (cold dessert), original chocolate (cold dessert). Kata Kunci : Kata kunci : Identifikasi, Hidangan untuk SPA (Solus Per Aqua). This study aims to Identify Dishes To SPA (Solus Per Aqua) in Lovina Tourism Region includes the type of dishes to SPA (Solus Per Aqua) from appetizer, main course and dessert. This research was conducted in Lovina Tourism Region by taking four (4) of the hotel as a place of research is Sunari Villa's And SPA Resort, Puri Saron, Bayualit Spa'n Resort and Spa Sundara Chocolate with research informants are the source of Cheff hotel Lovina Tourism Region. Data collection techniques by observation (observation) and interviews, while the research instrument used is the observation sheet and interview guides. Analysis of data using qualitative descriptive technique. The results showed that the dish for SPA (Solus Per Aqua) in Region Tourism Lovina (1) Sunari Villa's And SPA Resort, dish appetizers include tuna fish salad (cold appetizer), cream potato leek soup (hot appetizer), dish main course includes club house sandwich, BLT sandwiches, beef burgers and dessert dishes include sunari mixed juice (cold dessert) and Indonesian tea (hot dessert). (2) Bayualit Spa'n Resort dishes include mixed salad appetizer (cold appetizer), tomato saup with toas (hot appetizer) main course dishes include chicken sandwiches, club sandwiches and dessert dishes include mix juice (cold dessert), ginger tea (hot dessert). (3) puri saron, appetizer dishes include caesar salad (cold appetizer), cream of tomato soup (hot appetizer) main course dishes include sandwih club, and dessert dishes include banana juice (cold dessert) ginger tea (hot dessert). (4) Sundara Chocolate SPA, dish appetizer include potato salad (cold appetizer), cream chicken soup (hot appetizer) dish main course includes club sandwiches, smoke beef sandwiches, chicken barito and dessert dishes include ice ginger chocolate (cold dessert), daydreaming moctail (cold dessert), original chocolate (cold dessert). keyword : Keywords: Identification, Meals for SPA (Solus Per Aqua).